Impact of dietary lysine on growth, nutrient utilization, and intestinal health in triploid rainbow trout (Oncorhynchus mykiss) fed low fish meal diets - Shuze Zhang; Chang’an Wang; Siyuan Liu; Yaling Wang; Shaoxia Lu; Shicheng Han; Haibo Jiang; Hongbai Liu; Yuhong Yang (Aquaculture Reports)
Lysine is one of the essential amino acids for fish growth and development. This study investigated the effect of dietary lysine on growth performance, digestion, and intestinal health of triploid rainbow trout (Oncorhynchus mykiss) (initial body weight: 9.00 ± 0.33 g) fed a low fish meal diet (15 %). Five dietary lysine levels (3.66 %, 3.84 %, 4.19 %, 4.32 %, and 4.55 %) were evaluated for 56 days, with three replicates of 30 fish per level. The results showed that the weight gain rate (198.55 %), specific growth rate (1.95), and VSI were maximized when the dietary lysine level was 4.19 %. The 4.19 % lysine group exhibited minimum moisture (66.66 %) and maximum crude protein (15.47 %), with no significant differences in crude lipid and ash contents. Growth factors mTOR and 4EBP-1, on the other hand, had the highest expression in the 4.19 % group, while IGF-1 and S6K1 peaked in the 4.32 % group. The anti-inflammatory factors TGF-β, NF-κB, IL-4, and IL-10 peaked at different levels and then decreased with increasing lysine levels. The pro-inflammatory factor IL-1β, on the other hand, had the lowest expression at the 4.19 % level. Based on quadratic regression analysis of specific growth rate, the lysine requirement of triploid O. mykiss in low fish meal diets was 4.24 %.